Towards establishing peaceful co-existence between Buddhists and Muslims in Myanmar - Tun Aung, U (Kulliyah of Islamic Revealed Knowledge and Human Sciences International Islamic University Malaysia, 2010)
Muslims of Myanmar have been living in Myanmar for more than thousands of years without any visible problem. However, post independence period is the commencement of adversity for the Muslims as political and economic situation have deteriorated. Many unwanted disputes and conflicts between the Buddhists and the Muslims have occurred where innumerable volume of properties and lives belonging to the Muslims were perished. The objective of this research is to find out the root cause of the conflict and the possibilities of the settlement of the problem. The methodology of the research is aimed at the qualitative analysis through the library study and looking at relevant information based on books, articles, websites, newspapers, reports of various agencies including interviews of selected personalities. This study highlights the need for immediate reconciliation paving a way for settlement among conflicting parties: the junta, opposition parties and minorities including ethnic and religious groups. The establishment of peaceful coexistence between the Muslims and Buddhists can be achieved if the respective parties take their own responsibility without afflicting on other and exercising the win win situation.